An online testing method for optimal resin content of fuel cell catalyst layer
By measuring the mass-specific power density of the fuel cell catalyst and the roughness of the catalytic layer and calculating the mass-specific power density of the resin, the method of quickly judging the optimal resin content of the catalytic layer online is realized, and the problem of difficulty in quickly testing the optimal resin content in the prior art is solved, and the performance of the fuel cell is optimized.
Patent Information
- Application Number
- CN202110793496.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-07-13
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2041-07-13
AI Technical Summary
The prior art is difficult to quickly and easily test the optimal resin content in the fuel cell catalytic layer online, which affects the optimization of battery performance.
By measuring the mass-specific power density of the fuel cell catalyst and the roughness of the catalytic layer, the mass-specific power density of the resin is calculated, and the optimal resin content of the catalytic layer is quickly judged online.
A lossless, fast and simple online testing method is realized, which can quickly determine the optimal resin content of the catalytic layer, thereby optimizing the performance of the fuel cell.
Smart Images

Figure CN115616202B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of fuel cells, and in particular relates to a method for online testing of the optimum resin content in a catalyst layer of a fuel cell. Background Art
[0002] Under the background of carbon neutrality, the global popularization and application of hydrogen energy are accelerating, and the fuel cell industry based on the end of the hydrogen energy industry chain has also entered the fast lane of development. For fuel cell stacks, performance and cost are the key factors that determine whether they can be commercialized on a large scale. The membrane electrode is the core component of the fuel cell, which specifically includes a proton exchange membrane, a catalyst layer, a gas diffusion layer and a sealing layer. As the place where the electrochemical reaction occurs in the battery, the catalyst layer plays a decisive role in the battery performance. Generally speaking, the catalyst layer mainly contains two components, namely catalysts and resins, and the content of both affects the activity of the battery. Among them, the content of the catalyst determines the size of the three-phase area where the electrochemical reaction occurs in the catalyst layer, and the content of the resin affects both the oxygen mass transfer and proton conduction of the catalyst layer. For the catalyst layer, if the resin content is too low, the proton conduction in the catalyst layer is poor, and the overall battery performance is low; if the resin content is too high, the oxygen diffusion in the catalyst layer is hindered, and the oxygen mass transfer resistance increases, which makes the battery performance at high current density significantly reduced. Based on this, for a catalyst layer with a specific catalyst and loading, there is an optimal value for the resin content, that is, a fuel cell containing a catalyst layer with this resin content can achieve the best performance under the same test conditions.
[0003] However, since the effect of the resin content in the catalyst layer on the battery performance can only be obtained through the comparison of polarization curves and peak power density, it is time-consuming and laborious to prepare a single cell with a catalyst layer of different resin contents and conduct performance tests. Therefore, it is necessary to introduce an online test method for the optimal resin content of the catalyst layer. Summary of the invention
[0004] The present invention aims at the insufficiency of the existing method for determining the optimal resin content of the catalyst layer in fuel cell technology, and provides an online testing method for the optimal resin content of the catalyst layer of a fuel cell. The method has the advantages of being non-destructive, rapid, and simple, and the purpose of quickly determining the optimal resin content of the catalyst layer can be achieved by using the method.
[0005] The technical solution of the present invention is as follows:
[0006] An online testing method for the optimal resin content of a fuel cell catalyst layer comprises the following steps:
[0007] 1) Determination of fuel cell catalyst mass specific power density:
[0008] 2) Determination of roughness of fuel cell catalyst layer:
[0009] 3) Calculation of fuel cell resin mass specific power:
[0010] Based on the test results of the above two steps, calculate the resin mass specific power density P of the membrane electrode sample to be tested. ion. (kWg ion. -1 ), the calculation formula is as follows:
[0011] P ion. =Pr.fc Pt / ion. ×10 -6 (Formula 1)
[0012] Among them, P ion. (kW g ion. -1 ) is the resin mass specific power density of the fuel cell catalyst layer, P (kW g -1 ) is the mass power density of the fuel cell catalyst, rf is the roughness of the catalyst layer, c Pt / ion. is the mass ratio of catalyst to resin in the catalytic layer;
[0013] 4) Determination of the optimal resin content of the catalyst layer:
[0014] Based on the calculation results of the resin mass specific power in step 3, the optimal resin content of the catalyst layer of the fuel cell to be tested is determined: if 0.85≤P ion. ≤1.15, then the resin content of the catalyst layer to be tested is the optimal resin content. ion. <0.85, the resin content of the catalyst layer to be tested is less than the optimal resin content. ion. >1.15, the resin content of the catalyst layer to be tested is higher than the optimal resin content.
[0015] Based on the above scheme, preferably, in step 4), if 0.90≤P ion. ≤1.10, then the resin content of the catalyst layer to be tested is the optimal resin content. ion. <0.90, the resin content of the catalyst layer to be tested is less than the optimal resin content. ion. >1.10, the resin content of the catalyst layer to be tested is higher than the optimal resin content.
[0016] Based on the above scheme, preferably, the test method of the fuel cell catalyst mass specific power density is as follows: assemble the membrane electrode sample to be tested into a fuel cell single cell and place it on a battery evaluation platform, measure the battery polarization curve under given temperature, pressure, humidification and hydrogen / air flow conditions, and obtain the peak power density P of the battery. peak (kW cm -2 ), the fuel cell catalyst mass specific power density calculation formula is as follows:
[0017]
[0018] Among them, P (kW g -1 ) is the fuel cell catalyst mass specific power density, P peak (kW cm -2 ) is the peak power density of the fuel cell, g is the catalyst loading of the fuel cell catalyst layer (g cm -2 ).
[0019] Based on the above scheme, preferably, the test method of the roughness of the fuel cell catalyst layer is as follows: a cyclic voltammetry test is performed on the battery to be tested under a hydrogen / nitrogen atmosphere to calculate the electrochemically active specific surface area (ECSA, m 2 g Pt -1 ), the calculation formula of the roughness of the fuel cell catalyst layer is as follows:
[0020] rf=ECSA×g×10 (Formula 3)
[0021] Among them, rf is the roughness of the catalyst layer, ECSA (m 2 g -1 ) is the electrochemically active specific surface area of the catalyst layer, g is the catalyst loading of the fuel cell catalyst layer (mg cm -2 ).
[0022] The specific test and calculation methods for determining the ECSA of the battery in step 2) refer to Chapter 7 of "Fuel Cell Fundamentals" (by O'Hare, USA).
[0023] Based on the above solution, preferably, the resin contained in the catalyst layer is one or more resin materials selected from perfluorosulfonic acid resin and non-fluorosulfonic acid resin.
[0024] Based on the above scheme, preferably, the membrane electrode in step 1) can be prepared by the following method: the catalytic layer is prepared on the proton exchange membrane or gas diffusion layer by brushing, scraping, transfer, spraying, screen printing or inkjet printing to obtain the membrane electrode.
[0025] Compared with the prior art, the present invention has the following advantages:
[0026] 1. The method provided by the present invention can be used to test the optimal resin content in the catalyst layer of a fuel cell. The test method is easy to operate and has high feasibility;
[0027] 2. The detection method is convenient and quick. By testing the catalyst layer with any resin content, the difference between the resin content of the catalyst layer under the catalyst type and loading and the optimal resin content can be quickly determined, and the optimal resin content can be quickly determined;
[0028] 3. The test process is an online test and does not cause any damage to the fuel cell membrane electrode components. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The cathode Pt loading obtained in Example 1 is 0.4 mg cm -2 Polarization curve and power density curve of the battery.
[0030] Figure 2 The cathode Pt loading obtained in Example 1 is 0.4 mg cm -2 , the cyclic voltammetry curve of the battery with the catalyst layer resin content of I / C=0.3.
[0031] Figure 3 The Pt loading of the cathode obtained in Example 2 is 0.3 mg cm -2 Polarization curve and power density curve of the battery.
[0032] Figure 4 The Pt loading of the cathode obtained in Example 3 is 0.2 mg cm -2 Polarization curve and power density curve of the battery.
[0033] Figure 5 The cathode Pt loading obtained in Example 4 is 0.1 mg cm -2 Polarization curve and power density curve of the battery. DETAILED DESCRIPTION
[0034] Example 1
[0035] Using 70% Pt / C (Vulcan XC) as catalyst and 5% Nafion solution as resin solution, the Pt loading on the NR-211 membrane was sprayed with the anode / cathode being 0.2 / 0.4 mg cm -2 The resin content of the catalyst layer is: anode I / C = 0.7, cathode I / C = 0.3, 0.5, 0.7, 0.9, and the effective area is 5cm -2 The membrane electrode was assembled into a fuel cell and placed on a battery evaluation table. The test was carried out at 60°C, 200 kPa, 100% humidity, and an intake flow rate of hydrogen 100 ml min -1 、Air 800mlmin -1 The polarization curve of the battery under conditions such as Figure 1 , the peak power density P of the battery is obtained peak , respectively: 653.4, 685.2, 790.53, 337.3kW cm -2 ; and measured at 60℃, 101kPa, 100% humidity, and 80ml / min hydrogen inlet flow -1. Nitrogen 100ml min -1 The cyclic voltammetry curve of the battery under the conditions of 1 / C = 0.3 is shown in Figure 2. The roughness of the catalyst layer is 147.04, 142.00, 140.00, and 337.30 respectively. Figure 2 As shown in the figure, the electrochemically active specific surface area of the catalytic layer ECSA is calculated to be 36.76 m 2 g Pt -1 According to formula 3, the roughness of the catalyst layer is rf = 36.76 × 0.4 × 10 = 147.04; Based on the above test results, calculate the catalyst layer resin mass specific power density P ion. , respectively: 1.84, 1.16, 0.92, 0.23kW g ion. -1 .
[0036] From the above test results, it can be seen that when I / C = 0.7, the catalyst layer resin mass ratio power density P ion. 0.92kWg ion. -1 , this value is closest to 1, and the battery performance is optimal at this time, 790.53kW cm -2 Therefore, the optimal resin content of the catalyst layer is I / C = 0.7; when I / C = 0.3, 0.5, due to the low resin content, proton conduction is poor, and the battery performance is lower than that when I / C = 0.7. At this time, the catalyst layer resin mass is higher than the power density P ion. When I / C = 0.9, due to the high resin content and poor oxygen mass transfer, the battery performance is significantly lower than that when I / C = 0.7. At this time, the catalyst layer resin mass is higher than the power density P ion. Less than 1.
[0037] Example 2
[0038] Using 70% Pt / C (Vulcan XC) as catalyst and 5% Nafion solution as resin solution, the Pt loading on the NR-211 membrane was sprayed with the anode / cathode being 0.2 / 0.3 mg cm -2 , the resin content of the catalyst layer is: anode I / C = 0.7, cathode I / C = 0.3, 0.5, 0.7, 0.9, and the effective area is 5cm -2 The membrane electrode was assembled into a fuel cell and placed on a battery evaluation table. The test was carried out at 60°C, 200 kPa, 100% humidity, and an intake flow rate of hydrogen 100 ml min -1 、Air 800mlmin -1 The polarization curve of the battery under conditions such as Figure 2 , the peak power density P of the battery is obtainedpeak , respectively: 633.60, 660.84, 735.41, 282.18kW cm -2 ; and measured at 60℃, 101kPa, 100% humidity, and 80ml / min hydrogen intake flow -1 、Nitrogen 100ml min -1 The cyclic voltammetry curves of the battery under the conditions obtained the roughness of the catalyst layer, which were 119.34, 109.26, 114.00, and 68.52 respectively; based on the above test results, the catalyst layer resin mass specific power density P was calculated ion. , respectively: 1.94, 1.15, 0.93, 0.17kW g ion. -1 .
[0039] From the above test results, it can be seen that when I / C = 0.7, the catalyst layer resin mass ratio power density P ion. 0.93kWg ion. -1 , this value is closest to 1, and the battery performance is optimal at this time, 735.41kW cm -2 Therefore, the optimal resin content of the catalyst layer is I / C = 0.7; when I / C = 0.3, 0.5, due to the low resin content, proton conduction is poor, and the battery performance is lower than that when I / C = 0.7. At this time, the catalyst layer resin mass is higher than the power density P ion. When I / C = 0.9, due to the high resin content and poor oxygen mass transfer, the battery performance is significantly lower than that when I / C = 0.7. At this time, the catalyst layer resin mass is higher than the power density P ion. Less than 1.
[0040] Example 3
[0041] 70% Pt / C (Vulcan XC) was used as the catalyst and 5% Nafion solution was used as the resin solution. The Pt loading was sprayed on the NR-211 membrane by spraying method. The anode / cathode loading was 0.2 / 0.2 mg cm -2 The resin content of the catalyst layer is: anode I / C = 0.7, cathode I / C = 0.3, 0.5, 0.7, 0.9, and the effective area is 5cm -2 The membrane electrode was assembled into a fuel cell and placed on a battery evaluation table. The test was carried out at 60°C, 200 kPa, 100% humidity, and an intake flow rate of hydrogen 100 ml min -1 、Air 800mlmin -1 The polarization curve of the battery under conditions such as Figure 3 , the peak power density P of the battery is obtained peak, respectively: 610.61, 583.60, 304.00, 179.48kW cm -2 ; and measured at 60℃, 101kPa, 100% humidity, and 80ml / min hydrogen intake flow -1 、Nitrogen 100mlmin -1 The cyclic voltammetry curve of the battery under the conditions obtained the roughness of the catalyst layer, which is 41.01, 33.58, 55.02, 58.74 respectively; based on the above test results, the catalyst layer resin mass specific power density P is calculated ion. , respectively: 0.95, 0.47, 0.28, 0.14kW g ion. -1 .
[0042] From the above test results, it can be seen that when I / C = 0.3, the catalyst layer resin mass ratio power density P ion. 0.95kWg ion. -1 , this value is closest to 1, and the battery performance is the best at this time, 610.61kW cm -2 Therefore, the optimal resin content of the catalyst layer is I / C = 0.7; when I / C>0.3, due to the high resin content, the oxygen mass transfer is poor, and the battery performance is significantly lower than that when I / C = 0.37. At this time, the catalyst layer resin mass is higher than the power density P ion. Less than 1.
[0043] Example 4
[0044] 70% Pt / C (Vulcan XC) was used as the catalyst and 5% Nafion solution was used as the resin solution. The Pt loading was sprayed on the NR-211 membrane by spraying method. The anode / cathode loading was 0.2 / 0.1 mg cm -2 The resin content of the catalyst layer is: anode I / C = 0.7, cathode I / C = 0.3, 0.5, 0.7, 0.9, and the effective area is 5cm -2 The membrane electrode was assembled into a fuel cell and placed on a battery evaluation table. The test was carried out at 60°C, 200 kPa, 100% humidity, and an intake flow rate of hydrogen 100 ml min -1 、Air 800mlmin -1 The polarization curve of the battery under conditions such as Figure 4 , the peak power density P of the battery is obtained peak , respectively: 461.97, 453.78, 311.28, 178.00 kW cm -2 ; and measured at 60℃, 101kPa, 100% humidity, and 80ml / min hydrogen intake flow -1 、Nitrogen 100mlmin-1 The cyclic voltammetry curve of the battery under the conditions obtained the roughness of the catalyst layer, which is 30.00, 28.44, 26.73, and 25.17 respectively; based on the above test results, the catalyst layer resin mass specific power density P is calculated ion. , respectively: 1.07, 0.62, 0.28, 0.12kW g ion. -1 .
[0045] From the above test results, it can be seen that when I / C = 0.3, the catalyst layer resin mass ratio power density P ion. 1.07kWg ion. -1 , this value is closest to 1, and the battery performance is the best at 461.97kW cm -2 Therefore, the optimal resin content of the catalyst layer is I / C = 0.7; when I / C>0.3, due to the high resin content, the oxygen mass transfer is poor, and the battery performance is significantly lower than that when I / C = 0.37. At this time, the catalyst layer resin mass is higher than the power density P ion. Less than 1.
Claims
1. An online testing method for the optimal resin content of a fuel cell catalyst layer, characterized in that: The following steps are involved: 1) Determination of fuel cell catalyst mass specific power density: 2) Determination of roughness of fuel cell catalyst layer: 3) Calculation of fuel cell resin mass specific power: Based on the test results of step 1) and step 2), calculate the resin mass specific power density P of the membrane electrode sample to be tested ion. (kWg ion. -1 ), the calculation formula is as follows: P ion. =Pr.fc Pt / ion. ×10 -6 (Formula 1) Among them, P ion. (kW g ion . -1 ) is the resin mass specific power density of the fuel cell catalyst layer, P (kW g -1 ) is the mass power density of the fuel cell catalyst, rf is the roughness of the catalyst layer, c Pt / ion. is the mass ratio of catalyst to resin in the catalytic layer; 4) Determination of the optimal resin content of the catalyst layer: Based on the calculation result of the resin mass specific power in step 3), the optimal resin content of the catalyst layer of the fuel cell to be tested is determined: if 0.85≤P ion. ≤1.15, then the resin content of the catalyst layer to be tested is the optimal resin content. ion. <0.85, the resin content of the catalyst layer to be tested is less than the optimal resin content. ion. >1.15, the resin content of the catalyst layer to be tested is higher than the optimal resin content.
2. The testing method according to claim 1, characterized in that: In step 4), if 0.90≤P ion. ≤1.10, then the resin content of the catalyst layer to be tested is the optimal resin content. ion. <0.90, the resin content of the catalyst layer to be tested is less than the optimal resin content. ion. >1.10, the resin content of the catalyst layer to be tested is higher than the optimal resin content.
3. The testing method according to claim 1, characterized in that: The test method of the fuel cell catalyst mass specific power density is as follows: The membrane electrode samples to be tested are assembled into a single fuel cell and placed on a battery evaluation platform. The battery polarization curve under given temperature, pressure, humidification and hydrogen / air flow conditions is measured to obtain the peak power density P of the battery. peak (kW cm -2 ), the fuel cell catalyst mass specific power density calculation formula is as follows: Among them, P (kW g -1 ) is the fuel cell catalyst mass specific power density, P peak (kW cm -2 ) is the peak power density of the fuel cell, g is the catalyst loading of the fuel cell catalyst layer (g cm -2 ).
4. The testing method according to claim 1, characterized in that: The test method for the roughness of the fuel cell catalyst layer is as follows: The battery under test was subjected to cyclic voltammetry test in hydrogen / nitrogen atmosphere, and the electrochemically active specific surface area (ECSA, m 2 g Pt -1 ), the calculation formula of the roughness of the fuel cell catalyst layer is as follows: rf=ECSA×g×10 (Formula 3) Among them, rf is the roughness of the catalyst layer, ECSA (m 2 g -1 ) is the electrochemically active specific surface area of the catalyst layer, g is the catalyst loading of the fuel cell catalyst layer (mg cm -2 ).
5. The testing method according to claim 1, characterized in that: The resin contained in the catalyst layer is one or more of perfluorosulfonic acid resin and non-fluorosulfonic acid resin.
6. The testing method according to claim 3, characterized in that: The preparation method of the membrane electrode is: a catalyst layer is prepared on a proton exchange membrane or a gas diffusion layer by a brush coating method, a scraping method, a transfer method, a spray coating method, a screen printing method or an inkjet printing method to obtain the membrane electrode.
Citation Information
Patent Citations
Method for testing substitution degree of condensed silicon resin
CN112557640A
Resin content testing method and device based on time domain nuclear magnetic resonance
CN112858368A